Analisis Yuridis Tindak Pidana Peredaran Pupuk Tidak Terdaftar dalam Perspektif Hukum Positif Indonesia - Dita Dwi Angela Putri; Ismail Marzuki (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2026)
The distribution of unregistered fertilizers constitutes a criminal offense in the agricultural sector that may cause financial losses to farmers, reduce agricultural productivity, and threaten national food security. This study aims to analyze the legal regulation of criminal acts involving the distribution of unregistered fertilizers under Indonesian positive law and to examine the criminal liability of individuals or business entities that produce or distribute fertilizers without complying with statutory requirements. This research employs a normative legal research method using statutory, conceptual, and case approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed qualitatively through library research. The findings indicate that the regulation of fertilizer distribution in Indonesia is governed by Law Number 22 of 2019 concerning Sustainable Agricultural Cultivation Systems and its implementing regulations. Every fertilizer distributed in Indonesia must comply with quality standards, be officially registered, and obtain a valid distribution permit. Individuals or business entities that produce or distribute unregistered fertilizers may be held criminally liable if all elements of the offense stipulated by the applicable legislation are fulfilled. However, law enforcement in this field still faces several challenges, including weak supervision, limited institutional resources, and low legal awareness among business actors. Therefore, stronger supervision, improved inter-agency coordination, and greater legal compliance are necessary to prevent the circulation of unregistered fertilizers and to support the realization of a sustainable agricultural cultivation system.